The circadian clock protects against ionizing radiation‐induced cardiotoxicity. Issue 2 (10th January 2020) - Dakup, Panshak P.; Porter, Kenneth I.; Gajula, Rajendra P.; Goel, Peeyush N.; Cheng, Zhaokang; Gaddameedhi, Shobhan
ABSTRACT: Radiation therapy (RT) is commonly used to treat solid tumors of the breast, lung, and esophagus; however, the heart is an unintentional target of ionizing radiation (IR). IR exposure to the heart results in chronic toxicities including heart failure. We hypothesize that the circadian system plays regulatory roles in minimizing the IR‐induced cardiotoxicity. We treated mice in control (Day Shift), environmentally disrupted (Rotating Shift), and genetically disrupted ( Per 1/2 mutant) circadian conditions with 18 Gy of IR to the heart. Compared to control mice, circadian clock disruption significantly exacerbated post‐IR systolic dysfunction (by ultrasound echocardiography) and increased fibrosis in mice. At the cellular level, Bmal1 protein bound to Atm, Brca1, and Brca2 promoter regions and its expression level was inversely correlated with the DNA damage levels based on the state of the clock. Further studies with circadian synchronized cardiomyocytes revealed that Bmal1 depletion increased the IR‐induced DNA damage and apoptosis. Collectively, these findings suggest that the circadian clock protects from IR‐induced toxicity and potentially impacts RT treatment outcome in cancer patients through IR‐induced DNA damage responses.